Urban versus rural older adults: occupational balance and quality of life comparison - Emel Pekçetin; Serkan Pekçetin; Emine Sağlamoğlu; Gamze Ekici (BMC Geriatrics)
Abstract Background Occupational balance is a crucial concept in occupational therapy and is recognized as a vital component of health and well-being. The residential status may have a significant impact on the occupational balance (OB) and quality of life (QoL) of older adults. Methods A group of 107 older adults from the urban area (mean age: 69.80 ± 4.78 years), and 93 older adults from the rural area (mean age: 71.24 ± 6.79 years) were examined. OB of the participants was evaluated with the Occupational Balance Questionnaire 11-T (OBQ 11-T) The QoL of older adults assessed by the World Health Organization Quality of Life – OLD module (WHOQOL-OLD). Results The median OBQ11-T total score was 21.00 (7.00) in the urban area group and 20.00 (5.00) in the rural area group. Older adults residing in urban areas had higher scores in the OBQ 11-T total score, Item 1 = “Having enough things to do during a regular week”, Item 5 = “Have sufficient time for doing mandatory occupations”, and Item 11 = “Satisfaction with time spent in rest, recovery, and sleep” (p < .05). This suggests that older adults in urban areas may perceive a better balance in their activities. In contrast, rural residents had lower scores on these items, potentially reflecting fewer perceived opportunities for engaging in activities in a balanced manner. Older adults daily residing in urban areas had higher scores in the WHOQOL-OLD total score, WHOQOL-OLD Sensory Abilities Subtest, and WHOQOL-OLD Autonomy Subtest (p < .05). These findings indicate a higher QoL, particularly in sensory and autonomy-related aspects, for older adults in urban areas. Conversely, rural residents reported lower scores on these QoL subscales, which may be attributed to different environmental and lifestyle factors associated with rural living. Conclusions These findings indicated that residency status is an important variable for both OB and QoL of older adults. Occupational therapy interventions should consider special needs of older adults who live in rural areas. Trial registration The clinical trial number is not applicable.